Transit [videorecording (DVD)] - Petzold, Christian, 1960-; Petzold, Christian, 1960-; Rogowski, Franz; Beer, Paula, 1995-; Giese, Godehard, 1972-; Seghers, Anna, 1900-1983 (Music Box Films, 2019)
A man seeking to flee German-occupied France assumes the identity of a dead writer to take advantage of his Mexican visa, and while waiting for the departure, he meets the writer's estranged wife and falls in love with her.